Ameliorative effects of Cuscuta reflexa and Peucedanum grande on letrozole induced polycystic ovary syndrome in Wistar rats - Firdaus Kausar; Muzafar Ahmad Rather; Showkeen Muzamil Bashir; Rana M. Alsaffar; Showkat ul Nabi; Sofi Imtiyaz Ali; Pankaj Goswami; Ansar Ahmad; Summya Rashid; Adil Farooq Wali (Taylor & Francis Group, 2021)
Objectives The current study was designed to examine the therapeutic role of hydroalcoholic extract of Cuscuta reflexa Roxb (CRE) and Peucedanum grande C.B. Clarke (PGE) on letrozole (1 mg/kg) induced polycystic ovary syndrome (PCOS) in female Wistar albino rats. Methods PCOS rats were treated with CRE (280 mg/kg), PGE (140 mg/kg) or CRE + PGE p.o. for 3 weeks. Vaginal smears for phase of estrous cycle determination, serum levels of sex androgens, lipid profile, oxidative stress parameters and histopathology of ovarian tissues were investigated. Results Diestrous cycle days treated with CRE (group III) or PGE (group IV) decreased significantly (p < 0.05) compared to PCOS control animals (group II). Moreover, weight of uteri in PCOS animals treated with the plant extracts also increased significantly (p < 0.05) compared to that of group II animals. Histopathological examination showed the protective effect of the CRE and PGE indicated by the disappearance of ovarian cyst. Conclusion The study demonstrated that the CRE and PGE either alone or in combination hold a significant effect in letrozole induced PCOS rat models and could be useful in the management of reproductive and metabolic disorders related to PCOS.